Optimization of Valuation Models for AI Investment Projects and Decision Support - Lai, Lingyun (European Journal of AI, Computing & Informatics, 2025)
With the rapid development of artificial intelligence (AI) technology, investment in the field of AI has gradually become a capital hotspot. This paper explores the integration of AI project valuation and decision support systems, analyzes the core challenges of investment in AI, and proposes optimization paths, including building a flexible valuation framework, optimizing valuation methods, designing a comprehensive risk assessment system, and promoting the improvement of policies and regulations. It aims to improve the level of decision support, reduce investment risks, and promote the healthy development of the AI industry.